2003
DOI: 10.1093/jnen/62.12.1287
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Pathology in Alzheimer Disease: Correlation of Cerebral Amyloid Angiopathy and Arteriosclerosis/Lipohyalinosis with Cognitive Decline

Abstract: Background: Synaptic loss is a common feature in the neocortex and hippocampus in AD. Individuals with MCI, lacking a clinical diagnosis of AD, manifest a decline in synapse numbers in the hippocampus. It is unclear whether areas of neocortex also affected in AD display synaptic loss during this prodromal transitional stage. The inferior temporal gyrus (ITG) is considered tertiary association cortex with a special role in higher order visual function. It is an integral part of the visual association pathway th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
300
4
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(322 citation statements)
references
References 43 publications
14
300
4
4
Order By: Relevance
“…The long-term functional outcome of cerebral small vessel disease is characterized by a significantly increased risk of cognitive impairment (21). This might be explained by the fact that, in the presence of mild or severe arteriosclerosis/lipohyalinosis, there is simultaneous involvement of thalamic and cortical small vessels as shown in autopsy brains by Thal et al (22). Moreover, previous studies using PET (3, 4) have confirmed a reduction in the regional cerebral blood flow in the cortex and the thalami of elderly hypertensive brains.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term functional outcome of cerebral small vessel disease is characterized by a significantly increased risk of cognitive impairment (21). This might be explained by the fact that, in the presence of mild or severe arteriosclerosis/lipohyalinosis, there is simultaneous involvement of thalamic and cortical small vessels as shown in autopsy brains by Thal et al (22). Moreover, previous studies using PET (3, 4) have confirmed a reduction in the regional cerebral blood flow in the cortex and the thalami of elderly hypertensive brains.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,26 Although in some very severe cases, CAA can also be found in the deep gray-matter regions. 31 Radiologic manifestation of cerebral amyloid angiopathy: hemorrhagic and ischemic brain injury A definite diagnosis of CAA can only be made through biopsy or autopsy, however, clinical diagnostic criteria called the Boston criteria, allow researchers to diagnose CAA during life with high specificity (88% to 92%). 32,33 According to these criteria probable CAA is defined by the presence of multiple strictly lobar hemorrhages on T2* gradient-recalled echo or susceptibility weighted MRI.…”
Section: Pathologic Manifestation Of Cerebral Amyloid Angiopathymentioning
confidence: 99%
“…AD is known to have a vascular component, with small-vessel disease, microinfarction and cerebral amyloid angiopathy (characterised by Aβ deposition in vessel walls) [146][147]. Aβ plaques as well as retinal microvascular deposition of Aβ have been identified in the retinas of AD transgenic mouse models [133] and could possibly be detected by non-invasive optical scattering [110], Raman spectroscopic or fluorescent tagging techniques.…”
Section: (Figure 7)mentioning
confidence: 99%